(untitled) - Breemen, N. van. (Dordrecht,Boston, 2002)
Soil Formation deals with qualitative and quantitative aspects of soil formation (or pedogenesis) and the underlying chemical, biological, and physical processes. The starting point of the text is the process - and not soil classification. Effects of weathering and new formation of minerals, mobilisation, transport, and breakdown or immobilisation of dissolved and suspended compounds are discussed. Soil processes and profiles are discussed in relation to the landscape, the geosphere, and the biosphere. Emphasis lies on the universality of soil-forming processes in past and present, and on the soil as a dynamic entity that forms part of the total environment. Complexity of genetic processes in time and space is given much attention. The text gives many examples from literature and places some in a new light. The reader is guided through the subject matter by a large number of questions and problems to help understand and synthesis the material. Answers to all questions are included. This second edition has been updated to reflect recent discoveries. Printing errors have been corrected, and new photographs support the text. "Working through the questions and problems in this book would provide a rigorous training for any advanced pedology graduate student (and for many pedology professors as well)."(David J. Brown, Montana State University, Soil Science Vol. 169 No. 4)
Keywords: Soil formation,Cơ cấu đất